Interaction of power and business in Russia - Vladimir Moiseev; Victor Nitsevich; Oleg Sudorgin (Управление)
In order to successfully implement the ambitious socio-economic goals, set forth in the Address and in the May (2018) decree of the President V.V. Putin, including entering the TOP-5 of the world’s largest economies, reduce the poverty level of 10 million Russians, it is necessary, according to authors, to create comfortable conditions for doing business in our country, reducing and, if possible, eradicating raiding and corruption. This is a very difficult task, and it cannot be solved without close cooperation between the state and business. The purpose of this article is to study the problems of interaction between business and government in the light of the May (2018) decree of the state leader on the breakthrough socio-economic development of our country. To study the relationship between business and power in Russia, the authors have analyzed both positive aspects and shortcomings in this area, mainly related to corruption, lobbying, criminal prosecution of entrepreneurs, etc. Comparative, institutional, statistical and functional methods of analysis have been also used to reveal the main aspects of the theme. The application of the institutional method has allowed to analyze the role of the top Russian leadership and other authorities in the implementation of economic policy, the organization of interaction between power and business. The systemic, as well as structural and functional approaches contributed to the formation of a holistic and objective view of the state of business, the conditions for its conduct in our country, to the identification of both positive aspects and existing disadvantages in the implementation of governmental policy in this area. The method of comparative analysis was used by the authors to compare the volume of Russia’s gross domestic product (GDP) and other economic indicators with the economies of developed countries. The study resulted in some practical recommendations of the authors to improve the interaction of business and power in Russia, aimed at the further socio-economic development of our country in the context of tightening of Western sanctions.